Comparative study of micromixers for laminar blood mixing - Khalid, Khairul Nadiah (2013)
Miniaturization is the trend in analytical chemistry and life science. It has been emerging into the research field of microfluidics in the application of LOC. The application is used for biochemistry analysis and require a rapid mixing in small area. Due to laminar flow (Reynold Number < 1) passive micromixer is the best method in fluids mixing. Passive micromixer also depend on the channel geometry for mixing effectiveness. In this study, four different micromixers were evaluated based on the baseline control Y-micromixer. The micromixers are internal rib micromixer, patterned grooves micromixer, obstruction micromixer and slanted rib micromixer. These micromixer has 1000μm channel length, 150μm inlet length, 90o between inlets ports, width and depth are 40μm each. The fluids used for mixing were blood which has 1.0 × 10-6 kg/μms of viscosity and toluene which has low viscosity than blood (0.664 × 10-9 kg/μms). The fluids used to evaluate the differences in term of their visual performance based image’s standard deviation by plotting the graph and mixing efficiency by calculation. Based on these evaluations, the slanted rib micromixer is the best micromixer design with the highest mixing efficiency of 99.85% at the outlet of the channel.